Prevalence of putative virulence factors and antimicrobial susceptibility of Enterococcus faecalis isolates from patients with dental Diseases - Abu Hammad Osama; Dar-Odeh Najla; Salah Randa; Shehabi Asem A (BMC, 2008)
Abstract Background This study investigated the prevalence of Enterococcus faecalis, its putative virulence factors and antimicrobial susceptibility in individuals with and without dental diseases. A total of 159 oral rinse specimens were collected from patients (n = 109) suffering from dental diseases and healthy controls (n = 50). Results E. faecalis was detected using only culture in 8/109 (7.3%) of the patients with various types of dental diseases, whereas no E. faecalis was found in the healthy controls weather using both culture and PCR. Phenotype characterizations of the 8 E. faecalis isolates indicated that 25% of the isolates produced haemolysin and 37.5% produced gelatinase. Most important virulence genes; collagen binding protein (ace) and endocarditis antigen (efaA) were present in all 8 E. faecalis isolates, while haemolysin activator gene (cylA) was detected only in 25% of isolates, and all isolates were negative for esp gene. All E. faecalis isolates were 100% susceptible to ampicillin, chloramphenicol, ciprofloxacin, vancomycin, and teicoplanin, and to less extent to erythromycin (62.5%). Conclusion This study shows that all E. faecalis isolates were recovered only from patients with dental diseases especially necrotic pulps, and all isolates carried both collagen binding protein and endocarditis antigen genes and highly susceptible to frequently used antimicrobial drugs in Jordan.